Ecological Education as an Antidote to Degraded Nature - Falkowska, Anna (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2020)
It is common knowledge that life on Earth depends on natural resources: water, air, soil. All organisms are dependent on each other, like in a trophic chain. The need to protect the environment is a necessary measure that can ensure further development in all activities of human activities. The article contains analyzes of qualitative research - verification of documents that presented selected actions undertaken in the Capital City of Warsaw to show what has been done so far, which can be inspirational for environmental education for preventing degradation of nature by educators and decision-makers in other Polish cities. The publication contains information on teaching about ecology in the context of various educational models. It was important to verify the existing forms of teaching and presented the application of the basic principles of development by adults and children and adolescents. The sources of acquiring knowledge in the field of science education and examples of fun ones that will unite children have been included and their parents and will also help build a bond with nature to include environmental degradation. Community support can be an educational leader, which can be used in a variety of technologies, perhaps it will be able to support environmental policy to the culture of society living in the 21st century.